Updating the fossil record of the alligatoroid crocodylian Diplocynodon from the late Eocene of Transylvanian Basin - Venczel, Márton (Frontiers in Amphibian and Reptile Science, 2023)
The basal alligatoroid crocodylian Diplocynodon kochi erected for incomplete three-dimensional skull from the late Eocene (Priabonian) Cluj Limestone Formation in Romania, represents one of the easternmost distributed European members of Diplocynodontidae. New isolated cranial and postcranial remains provide new insights into the diagnostic features, phylogenetic relationships and lifestyle of this taxon, extending its fossil record to four new localities situated on the north-western side of the Transylvanian Basin. Diagnostic traits of the holotype include an extended insertion surface of jaw adductors on the parietal and squamosal, whereas the newly referred mandibles possess an enlarged and procumbent first dentary tooth, and the posterior teeth and alveoli are mediolaterally compressed. These attributes might have been related to the prey capture approach of D. kochi, involved undoubtedly in the food chains of both continental (fluvial or marshy-lacustrine) and shallow marine environments, as indicated by the taphonomic settings of the surveyed fossil bearing deposits. The warm and humid climate is indicated for the late Eocene (Priabonian) of the Transylvanian Basin based on palynomorphs, however, the presence of “growth rings” and “lines of arrested growth” on the prezygapophyses of a dorsal vertebra referred to D. kochi, points to a seasonal climate, installed well before the Eocene–Oligocene terminal event. Positioned between western and eastern European faunas, the diplocynodontid populations from the Transylvanian Basin survived probably the Eocene–Oligocene transition, as suggested by the early Oligocene (Rupelian) fossil record from the area.